Initial community perspectives on the Health Service Extension Programme in Welkait, Ethiopia - McAuliffe Eilish; Negusse Haile; MacLachlan Malcolm (BMC, 2007)
Abstract Background The Health Service Extension Programme (HSEP) is an innovative approach to addressing the shortfall in health human resources in Ethiopia. It has developed a new cadre of Health Extension Workers (HEWs), who are charged with providing the health and hygiene promotion and some treatment services, which together constitute the bedrock of Ethiopia's community health system. Methods This study seeks to explore the experience of the HSEP from the perspective of the community who received the service. A random sample of 60 female heads-of-household in a remote area of Tigray participated in a structured interview survey. Results Although Health Extension Workers (HEWs) had visited them less frequently than planned, participants generally found the programme to be helpful. Despite this, their basic health knowledge was still quite poor regarding the major communicable diseases and their vectors. Participants felt the new HESP represented an improvement on previous health provision. HEWs were preferred over Traditional Birth Attendants for assistance with labour Conclusion While the introduction of HEWs has been a positive experience for women living at the study site, the frequency of visits, extent of effectively imparted health knowledge and affects of HEWs on other health providers needs to be further explored.